2009
DOI: 10.1029/2008jf001170
|View full text |Cite
|
Sign up to set email alerts
|

Marine ice sheet dynamics: Hysteresis and neutral equilibrium

Abstract: [1] The stability of marine ice sheets and outlet glaciers is mostly controlled by the dynamics of their grounding line, i.e., where the bottom contact of the ice changes from bedrock or till to ocean water. The last report of the Intergovernmental Panel on Climate Change has clearly underlined the poor ability of models to capture the dynamics of outlet glaciers. Here we present computations of grounding line dynamics on the basis of numerical solutions of the full Stokes equations for ice velocity, coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
239
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(265 citation statements)
references
References 34 publications
(58 reference statements)
15
239
3
Order By: Relevance
“…He demonstrated that (1) marine ice sheets do not exhibit neutral equilibrium, but have well-defined, discrete equilibrium profiles; (2) steady grounding lines cannot be stable on upward-sloping beds; (3) marine ice sheets with overdeepened beds can undergo hysteresis under variations in sea level, accumulation rate, basal slipperiness and ice viscosity. Robison et al (2009) confirmed the stability of the grounding line on a downward bed slope comparing fluid-mechanical experiments and model results (with time-dependent evolution of the grounding line), while Durand et al (2009a) demonstrated the instability of marine ice sheets on upsloping beds with a Full Stokes (Elmer/Ice) model.…”
Section: Introductionsupporting
confidence: 48%
See 4 more Smart Citations
“…He demonstrated that (1) marine ice sheets do not exhibit neutral equilibrium, but have well-defined, discrete equilibrium profiles; (2) steady grounding lines cannot be stable on upward-sloping beds; (3) marine ice sheets with overdeepened beds can undergo hysteresis under variations in sea level, accumulation rate, basal slipperiness and ice viscosity. Robison et al (2009) confirmed the stability of the grounding line on a downward bed slope comparing fluid-mechanical experiments and model results (with time-dependent evolution of the grounding line), while Durand et al (2009a) demonstrated the instability of marine ice sheets on upsloping beds with a Full Stokes (Elmer/Ice) model.…”
Section: Introductionsupporting
confidence: 48%
“…Conversely, for MG models, changes in grounding line position are generally small and reversible. However, the models based on shallow-ice approximation used by Vieli and Payne lack a second independent boundary condition that is needed to accurately represent grounding line migration (see below ;Schoof 2007a;Durand et al 2009a), and although MG models generally produce more consistent results, a major drawback remains the complexity to implement in a threedimensional ice sheet model (Vieli and Payne 2005).…”
Section: Numerical Approachesmentioning
confidence: 99%
See 3 more Smart Citations